Implementation of Law Enforcement in Environmental Aspects By Undang-undang Number 6 Year 2023 - Deni Yusup Permana; Karmenita; Nur Rahmat (Eastasouth Institute, 2023)
The abstract addresses the low awareness of environmental conservation in Indonesia, as showed by the Environmental Performance Index 2022 (EPI) report. Based on Undang-undang Number 6 Year 2023, this study seeks to investigate the use of law enforcement in environmental elements. The research method involves a literature study approach and a normative juridical approach. The results and discussion highlight the regulations and articles in Undang-undang Number 6 Year 2023 related to environmental law enforcement, including law enforcement authorities, administrative and criminal sanctions, and dispute resolution mechanisms. The implementation of good law enforcement can positively affect environmental protection and preservation. However, improper implementation may lead to negative consequences, such as the criminalization of people living near protected environmental areas. The study emphasizes the role of law enforcement agencies in the implementation of Undang-undang Number 6 Year 2023 and the control and prevention of environmental damage through licensing mechanisms. It also stresses the importance of protecting people's rights in a healthy and sustainable environment. The conclusion emphasizes the need for increased awareness, commitment, and effective environmental law enforcement mechanisms to address environmental problems and prioritize sustainable development in Indonesia.